Ghibli Coffee / Amira Syakira Mohamad - Mohamad, Amira Syakira (2020)
In order to fulfil Fundamental of Entrepreneurship (ENT300) course requirement, I need to make a case study towards an enterprise. Throughout this case study, I have to collect all information about that enterprise in order to complete this study case. I have decided to choose Ghibli Coffee as my case study and already contact Mr Adib. From the online interview that I have make, I have more knowledge about Ghibli Coffee’s information likes their background of the business, organizational structure, entrepreneurial characteristics, products and characteristic of entrepreneurial and not included the appendices.